2014
DOI: 10.1111/nicc.12067
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of enteral nutrition in intensive care unit patients by a nurse‐driven feeding protocol

Abstract: Adherence to guidelines regarding early start and timely escalation of EN can be improved if ICU nursing staff is responsible for translating it into action with the help of a written algorithm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 41 publications
1
26
0
5
Order By: Relevance
“…Such protocolized care may also create a standard unit-based practice that bedside professionals (e.g., nurse or respiratory therapist) implement or override as needed. These have been used in the prevention of device-related infections [2534] and nutrition management [3537]. …”
Section: Recently Examined Use Of Defaults In Critical Care Medicinementioning
confidence: 99%
“…Such protocolized care may also create a standard unit-based practice that bedside professionals (e.g., nurse or respiratory therapist) implement or override as needed. These have been used in the prevention of device-related infections [2534] and nutrition management [3537]. …”
Section: Recently Examined Use Of Defaults In Critical Care Medicinementioning
confidence: 99%
“…These protocols can greatly improve nutrition outcomes and work efficiency . In an acute setting these protocols also empower nursing staff to independently initiate and escalate EN support, and assist with troubleshooting . One study evaluating a transition feeding protocol (TFP) in the critical care setting concluded that the use of a TFP from parenteral nutrition (PN) to EN increased the proportion of patients meeting nutritional adequacy; while another in the same setting reported improved patient nutrition status and nurses’ awareness on nutrition support for a protocol from PN to EN/ON .…”
Section: Introductionmentioning
confidence: 99%
“…Underfeeding is of concern because it has been associated with worse clinical outcomes, including mortality . Strategies to overcome nutrition deficits caused by interruptions have been developed to improve EN delivery …”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20][21][22][23] Strategies to overcome nutrition deficits caused by interruptions have been developed to improve EN delivery. [24][25][26][27] Volume-based EN (VBEN) is one strategy used to compensate for EN interruptions. 24,[28][29][30][31][32][33][34][35][36] VBEN uses an order for 24 hours (eg, 1200 mL/24 h) vs the traditional hourly infusion rate with rate-based EN (RBEN; eg, 50 mL/h).…”
Section: Introductionmentioning
confidence: 99%